Pengaruh Brand Image, Brand Love, Brand Trust Dan Kualitas Produk Terhadap Keputusan Pembelian Sepatu Ventela (Studi Kasus Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang Angkatan 2019-2020) - Vira Naila Solikha; Muhammad Ridwan Basalamah; Nanik Wahyuningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine the effect of brand image, brand love, brand trust and product quality on the decision to purchase ventella shoes in Students of the Faculty of Economics and Business, Islamic University of Malang, class of 2019-2020. The sampling technique using purposive sampling obtained a sample of 110 respondents. Methods of data collection using a questionnaire. The data analysis technique used in this study is multiple linear regression. The results of the study show that simultaneously brand image, brand love, brand trust and product quality have a positive and significant effect on purchasing decisions. Likewise partially brand image, brand love, brand trust, and product quality have a positive and significant effect. Keywords: Brand Image, Brand Love, Brand Trust, Product Quality, Purchase Decision.